Carbon ion irradiation plus CTLA4 blockade elicits therapeutic immune responses in a murine tumor model. (1st December 2022) - Hartmann, Laura; Osen, Wolfram; Eichmüller, Oliver L.; Kordaß, Theresa; Furkel, Jennifer; Dickes, Elke; Reid, Carissa; Debus, Jürgen; Brons, Stephan; Abdollahi, Amir; Moustafa, Mahmoud; Rieken, Stefan; et al.
Abstract: Radiotherapy can act as an in situ vaccine, activating preventive tumor-specific immune responses in patients. Although carbon ion radiotherapy has superior biophysical properties over conventional photon irradiation, the immunological effects induced by this radiation type are poorly understood. Multiple strategies combining radiotherapy with immune checkpoint inhibition (radioimmunotherapy) to enhance antitumor immunity have been described; however, immune cell composition in tumors following radioimmunotherapy with carbon ions remains poorly explored. We developed a bilateral tumor model based on time-shifted subcutaneous injection of murine Her2+ EO771 tumor cells into immune-competent mice followed by selective irradiation of the primary tumor. αCTLA4-, but not αPD-L1-based radioimmunotherapy, induced complete tumor rejection and mediated the eradication of even non-irradiated, distant tumors. Cured mice were protected against the EO771 rechallenge, indicating long-lasting, tumor-specific immunological memory. Single-cell RNA sequencing and flow cytometric analyses of irradiated tumors revealed activation of NK cells and distinct tumor-associated macrophage clusters with upregulated expression of TNF and IL1 responsive genes. Distant tumors in the irradiated mice showed higher frequencies of naïve T cells activated upon the combination with CTLA4 blockade. Thus, radioimmunotherapy with carbon ions plus CTLA4 inhibition reshapes the tumor-infiltrating immune cell composition and can induce complete rejection even of non-irradiated tumors. Our data suggest combining radiotherapy approaches with CTLA4 blockade to achieve durable antitumor immunity. Evaluation of future radioimmunotherapy approaches should not be restricted to immunological impact at the irradiation site but should also consider systemic immunological effects on non-irradiated tumors. Highlights: Radioimmunotherapy induced effects are studied in a novel bilateral tumor model. Carbon ion irradiation causes intratumoral conversion of the myeloid compartment, while promoting accumulation of NK cells. Distant non-irradiated tumors show enhanced proportions of activated CD8 + T cells upon CTLA4 blockade. Radioimmunotherapy employing CTLA4 inhibition is superior to combination with PD-L1 blockade. Combination therapy causes long lasting protection against tumor rechallenge.